Reforma al articulo 469 del Código Orgánico de organización territorial, autonomía y descentralización sobre el levantamiento de las prohibiciones de enajenar en los distritos metropolitanos por obras de urbanización en zonas en riesgo - Sangoquiza Lasso, Tatiana Maritza (2014)
The present research is based on legal principles and focuses on the establishment of measures to control the indiscriminate growth of human settlements in high risk areas within the metropolitan districts , amending article 469 of the Organic Code of Territorial Organization , Autonomy Decentralization and on the disposition of properties affected - . "Whoever alienates land or buildings affected by the land use plan must state that fact in the appropriate title transfer and also the commitments acquired with any municipality or metropolitan district”. The creation of ordinances adopted neighborhood social interest , has allowed the location of housing recognized as high mitigated and not mitigated risk sectors due to their physical locations , with the goal of creating a culture of planning in the tidying of these sectors metropolitan districts within its provisions have settled to maintain " dispose bans until the works culminate in these neighborhoods ," which has caused problems in the landholders and has engulfed the Districts in the same game , since not able to lift the bans, these districts cannot proceed with the expropriation of such properties that have been declared high risk cannot be mitigated and mitigated .